Aerosolized Antibiotics for Ventilator-associated Pneumonia - Jean‐Jacques Rouby; Bélaïd Bouhemad; Antoine Monsel; Hélène Brisson; Charlotte Arbelot; Qin Lü (2012)
The aim of this review is to perform a critical analysis of experimental studies on aerosolized antibiotics and draw lessons for clinical use in patients with ventilator-associated pneumonia. Ultrasonic or vibrating plate nebulizers should be preferred to jet nebulizers. During the nebulization period, specific ventilator settings aimed at decreasing flow turbulence should be used, and discoordination with the ventilator should be avoided. The appropriate dose of aerosolized antibiotic can be determined as the intravenous dose plus extrapulmonary deposition. If these conditions are strictly respected, then high lung tissue deposition associated with rapid and efficient bacterial killing can be expected. For aerosolized aminoglycosides and cephalosporins, a decrease in systemic exposure leading to reduced toxicity is not proven by experimental studies. Aerosolized colistin, however, does not easily cross the alveolar-capillary membrane even in the presence of severe lung infection, and high doses can be delivered by nebulization without significant systemic exposure.